Physical activity moderates the association between executive function and functional connectivity in older adults - Marissa A Gogniat; Talia L Robinson; Kharine R Jean; L Stephen Miller (Aging Brain, 2022)
Recent evidence suggests that physical activity may influence the functional connectivity of the aging brain. The purpose of this study was to examine the influence of physical activity on the association between executive function and functional connectivity of key brain networks and graph theory metrics in community-dwelling older adults. Participants were 47 older adults (M = 73 years; SD = 5.92) who participated in neuropsychological testing, physical activity measurements, and magnetic resonance imaging (MRI). Seed-to-voxel moderation analyses and graph theory analyses were conducted. Physical activity was significantly positively associated with default mode network functional connectivity (DMN FC; Posterior Cingulate Gyrus, p-FDR = 0.005; Frontal Pole (L), p-FDR = 0.005; Posterior Cingulate Gyrus, p-FDR = 0.006; Superior Frontal Gyrus (L), p-FDR = 0.016) and dorsal attention network functional connectivity (DAN FC; Inferior Frontal Gyrus Pars Opercularis (R), p-FDR = 0.044). The interaction between physical activity and executive function on the DMN FC and DAN FC was analyzed. The interaction between executive function and physical activity was significantly associated with DMN FC. When this significant interaction was probed, the association between physical activity and DMN FC differed between levels of high and low executive function such that the association was only significant at levels of high executive function. These results suggest that greater physical activity in later life is associated with greater DMN and DAN FC and provides evidence for the importance of physical activity in cognitively healthy older adults.